Analisis Simulasi Antrian Produksi Beton pada Mesin Spinning di PT. ABC Menggunakan Software Arena - Hardiyansah, Robi; Luthfianto, Saufik (Universitas Kadiri, 2025)
PT. ABC is a company engaged in manufacturing precast concrete products. However, during production, the spinning stacking process causes disruptions due to queue buildup, resulting in longer production times. The spinning process distributes concrete strength and compacts concrete using a centrifugal system. This study aims to develop a queue model for the spinning process line using Arena simulation and evaluate queue reduction scenarios. In the first improvement proposal, adjustments reduce waiting time to the machine take four minutes. Machine 2 takes one and three minutes. Within the moment change proposition, by including one generation line. In second improvement proposal, by adding one production line, waiting time further decreases to 2 minutes for machine 1 and 0.65 minutes for machine 2. These simulation results demonstrate the effectiveness of optimizing production lines to reduce queuing delays. The findings provide valuable insights into queue modeling and process improvement in precast concrete production using simulation techniques. This study contributes to the understanding of queue management and operational efficiency in manufacturing environments, specifically within the spinning process of concrete production.